2020
DOI: 10.3389/fcell.2020.00568
|View full text |Cite
|
Sign up to set email alerts
|

rDNA Chromatin Activity Status as a Biomarker of Sensitivity to the RNA Polymerase I Transcription Inhibitor CX-5461

Abstract: Son et al. Active rDNA Chromatin and CX-5461 inactive rDNA repeats may serve as a biomarker to identify cancer patients who will benefit from CX-5461 therapy in future clinical trials. The data also reinforces the notion that rDNA instability is a threat to genomic integrity and cellular homeostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 66 publications
3
11
0
Order By: Relevance
“…Consistent with our results, active transcription of rDNA repeats has been found to enhance the sensitivity of cells to CX-5461 and DNA damage production (95). In cells, topological stresses induced by transcription are mainly resolved by the TOP1 protein (81).…”
Section: Transcription Drives Top2-dependent G4-ligand-induced Dsbssupporting
confidence: 91%
“…Consistent with our results, active transcription of rDNA repeats has been found to enhance the sensitivity of cells to CX-5461 and DNA damage production (95). In cells, topological stresses induced by transcription are mainly resolved by the TOP1 protein (81).…”
Section: Transcription Drives Top2-dependent G4-ligand-induced Dsbssupporting
confidence: 91%
“…We have also shown that high rates of Pol I transcription and active rDNA chromatin status determine sensitivity to CX-5461 in OvCa cell lines . 9 MYC is a master regulator of Pol I transcription and we have shown that upregulation of Pol I transcription is required to drive malignant transformation in MYC-driven lymphoma. 10 Our data therefore suggest MYC-driven Pol I transcription and/or MYC-driven global transcription and replication stress underlie sensitivity to CX-5461.…”
Section: Cx-5461-induced Replication Stress Targets Fork Stability Inmentioning
confidence: 94%
“…The rationale for targeting ribosome biogenesis in cancer is based on experimental and clinical evidence showing that tumorigenesis is associated with quantitative increases in ribosome production and/or production of qualitatively-altered ribosome species [44,45,47,48,52,[170][171][172][173]. These characteristics have formed the basis for the development of new drugs that disrupt the activation of rRNA synthesis by directly targeting the formation and activity of the RNA pol I transcriptional complex on rDNA [51,[174][175][176]. Effective ribosome biogenesis inhibition in cancer cells has gained considerable attention with the development of the two inhibitors, CX-5461 and CX-3543, which selectively bind to rDNA-enriched G-quadruplex regions and halt ribosome production [51,175].…”
Section: Targeting Ribosome Rna Synthesis In Colorectal Cancermentioning
confidence: 99%